The Role of Female Legislators in Communicating Mainstream Gender Policies - Kiswondari Kiswondari; Nur Kholisoh (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2024)
Since the stipulation of the 30% quota for women to the Indonesian House of Representatives, the number of female legislators in the Indonesian House of Representatives has increased significantly. However, this condition is not comparable to the birth of policies or legislative products that mainstream gender. This study aims to determine female legislators' perspectives, roles, and obstacles in communicating the Draft of the Maternal and Child Welfare Bill as a mainstream gender policy, using three key concepts of standpoint theory. This study uses a constructivist paradigm with a qualitative approach and case study method. The study's results found several things in the three key concepts of standpoint theory. Female legislators as political communicators have a broad perspective (standpoint) and situated knowledge in communicating mainstream gender policies. However, the gender perspectives of these female legislators have not been optimally communicated, so the provisions for extending maternity leave for working mothers for 6months and 40 days of leave for fathers, which are underlined in this bill, ultimately failed to be agreed upon.